Country-of-Origin Effects of Foreign Investments in the People's Republic of China - Schroath, Frederick W.; Hu, Michael Y.; Chen, Haiyang (Journal of International Business Studies, 1993)
This paper investigates the existence of country-of-origin effects occurring in foreign investments in the People's Republic of China. The eclectic theory of international production posits that the pattern of foreign investments should vary by country of origin. This aspect of the eclectic theory is difficult to test directly, especially in developing countries, because of the relatively small numbers of foreign investment projects in a single country. The data used in this research cover 1,665 Sino-foreign joint ventures (JVs) from 1979 to 1985, allowing a more reliable test of this aspect of the theory. Statistical evidence suggests that country-of-origin effects are indeed present in foreign investment activities in China.